PENGARUH MOTIVASI INTRINSIK, KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN LABUHANBATU SELATAN - Derwana .; Khoiruddin Harahap; Ahmad Zubeir; Astuty Leonia; Mahmud Salim Harahap (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The problems in research what is influence of intrinsic motivation on performance. What is influence of  leadership on performance. What is influence of job dicipline on performance. What is influence of intrinsic motivation,  leadership and job dicipline on performance. The research of purposes is for know and analysis influence of intrinsic motivation on performance. For know and analysis influence of  leadership on performance. For know and analysis influence of job dicipline on performance. For know and analysis influence of intrinsic motivation,  leadership and job dicipline on performance. Samples in the  research amount to 36 employees people. Data analyze technique in the research using descriptive analyze and regression analize. The results of this research explain of intrinsic motivation variable effect significant and positive on performance.  leadership variable effect significant and positive on performance. Job dicipline variable effect significant and positive on performance. Intrinsic motivation,  leadership and job dicipline variable effect significant and positive on performance.